Conventional Radiological Profile of Metastatic Bone Disease Based on Its Histopathological Results: A 3-Year Experience - Armando, Braven; Setiawati, Rosy; Edward, Mouli; Mustokoweni, Sjahjenny (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. The incidence of MBD tends to be more frequent in older ages and in female patients.2. The radiological appearance of a lesion tends to differ depending on its primary tumor.3. Pathological fracture was present in 55.37% of the cases. AbstractIntroduction: Metastasis commonly occurs in the bone, termed metastatic bone disease (MBD). Early diagnosis and intervention are important to prolong and increase the quality of life. Although conventional radiology is less sensitive for diagnosing this disease, it remains the most cost and time-efficient screening method. This study aimed to describe the radiological profile of patients diagnosed with MBD based on its histopathological result.Methods: This was a descriptive retrospective study using medical records and digital radiological data of patients diagnosed with MBD from 2019-2021 in Dr. Soetomo General Academic Hospital, Surabaya. Variables in this study include gender, age, histopathological result, location of metastases, number of lesions, lesion density, and pathological fracture.Results: 51 patients were diagnosed with MBD during the period of the study and sorted into 121 cases based on metastases location. MBD is more frequent in older female patients, where lesion mostly originates from the breast, thyroid, and lungs, with adenocarcinoma as the most common histology. Vertebrae were the most common location of metastases. Most lesion tends to be multiple and osteolytic. However, certain lesions from different primary tumor had different predilections. Pathological fracture was present in 55.37% of cases.Conclusion: MBD needs to be suspected in patients with cancer from the breast, thyroid, and lungs as its incidence is higher. More studies about MBD profiles on a larger scale should be conducted to better represent this disease in the general population.